Essays on trade policy - Ogeda, Pedro Molina (2024)
This thesis consists of three independent chapters. The first chapter show that the Brazilian trade liberalization in the early 1990s led to a permanent relative decline in the vote share of left-wing presidential candidates in the regions more affected by the tariff cuts. This happened even though the shock, implemented by a right-wing party, induced a contraction in manufacturing and formal employment in the more affected regions, and despite the left’s identification with protectionist policies. To rationalize this response, we consider a new institutional channel for the political effects of trade shocks: the weakening of labor unions. We provide support for this mechanism in two steps. First, we show that union presence—proxied by the number of workers directly employed by unions, by union density, and by the number of union establishments—declined in regions that became more exposed to foreign competition. Second, we show that the negative effect of tariff reductions on the votes for the left was driven exclusively by political parties with historical links to unions. Furthermore, the impact of the trade liberalization on the vote share of these parties was significant only in regions that had unions operating before the reform. These findings are consistent with the hypothesis that tariff cuts reduced the vote share of the left partly through the weakening of labor unions. This institutional channel is fundamentally different from the individual-level responses, motivated by economic or identity concerns, that have been considered in the literature. The second chapter examines the indirect effects of the U.S.-China trade war on the Brazilian labor market. We exploit the tariff increases across industries and the sectoral employment distribution across local labor markets to measure the degree of exposure of a Brazilian region to the trade war. Our findings reveal that while American discriminatory tariffs did not significantly impact Brazilian local labor markets, regions more exposed to Chinese retaliatory tariffs experienced a relative increase in the number of formal workers and wage bills. Additionally, we find that industries more exposed to Chinese duties experienced an increase in net exports. In contrast, industries exposed to American tariffs experienced a relative reduction in net exports. These insights contribute to a better understanding of the intricate worldwide implications of the U.S.-China trade war. The last chapter examines the impacts of Mercosur on Brazilian local labor markets. Our analysis reveals that the increasing export opportunities due to the preferential tariff reductions implemented by Argentina, Paraguay and Uruguay led to an increase in the number of formal workers in Brazil’s most exposed regions compared to the less exposed ones. Interestingly, we also find that Brazil’s preferential tariffs on its Mercosur partners relatively increased earnings premia in harder-hit regions. Furthermore, given that Brazilian unilateral trade liberalization coincided with the establishment of Mercosur, we also investigate whether the existing literature’s findings on the negative effects of Brazilian unilateral liberalization on labor markets hold when accounting for Mercosur tariff reductions. Our findings indicate that the impact is even more pronounced when considering the Mercosur.